Conditional stability for a class of second-order differential equations - Avramescu, C; Mustafa, OG; Rogovchenko, SP; Rogovchenko, YV (Pergamon-Elsevier Science Ltd, 2005)
Using two classes of test functions introduced recently by the authors, a criterion for conditional stability of the trivial solution of a second-order semi-linear differential equation is established. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: semi-linear differential equations; second order; asymptotic behaviour; test functions; conditional stability